Violencia doméstica y su relación con el intento de suicidio en las mujeres que asisten a la sala de primera acogida del Hospital Isidro Ayora de la ciudad de Loja, año 2015 - Macas Ordóñez, Eugenio Fabián (2015)
The domestic violence affects to all the family members, generating repercussions to the victims on their physical, mental or social health. The present investigative work wants to determine the relationship between domestic violence and the development of suicide ideation; as well to know the reasons that generate the different types of aggression. it was necessary to take information of 30 women who were attended on the “Sala de Primera Acogida”; of Isidro Ayora Hospital. The investigation uses a scientific social-type, guided by methods as inductively, deductively, analytical - synthetically; between the instruments of compilation of information there was a structured survey elaborated by the investigator, as well as the " Escala de Ideacion Suicida" elaborated by Aaron Beck, who allows to evaluate the trend to the suicide. In agreement to the obtained results, it is possible to demostrate that the lack of communication, unemployment, alcoholism and male chauvinism; are the most common reasons of violence; In this way also it was possible to state the majority of people presents alterations in his physical health in comparison with the psychological and social health. With this it was possible to elaborate a psychological educative plan directed to the victims of domestic violence in order to avoid a possible suicidal conduct. Key Words: Familiar circle, Victim, suicide ideation, trend to the suicide, lack of communication, male chauvinism, psychological health, psychological educative plan